Gambling-Motivated Attention and Improved Market Efficiency - Khanthavit, Anya (Thailand and The World Economy, 2025)
Information is incorporated into stock prices when investors trade; consequently, prices respond only to the information investors pay attention to. Because market efficiency requires rapid information dissemination and fully informative prices, attention necessarily affects the level of market efficiency. This study examines the role of retail investors’ market attention in determining the Stock Exchange of Thailand’s market efficiency. This unobservable market attention is measured using the Google search volume index for H̄ûn thịy or Thai stock and a daily sample ranging from August 6, 2008, to March 31, 2023 (3,573 observations). The autocorrelation test does not contradict the efficient market hypothesis, indicating that market attention neither improves nor reduces efficiency. Attention is then decomposed into two components: investment- and gambling-motivated attention. Additional testing of these two components shows that the nonsignificant result against the null hypothesis is the net effect of the inefficiency and improved efficiency induced by gambling-motivated attention. Noise trading induced by gambling-motivated attention plays an important role in improving efficiency by attracting the attention of sophisticated institutional investors. These investors then aggressively search for information to trade against and benefit from retail investors. The resulting trades incorporate new information into prices, improving efficiency.